Multisensory integration, body representation and somatic symptom experience in the general population - Ratcliffe, Natasha (2017)
Experience of the bodily self is dependent upon the integration of current sensory signals with existing knowledge and prior expectations about the body. As such, the way in which the self is perceived is not a direct reflection of the body’s actual state, but rather an interpretation of available sensory information. The phenomena of “medically unexplained symptoms” provide an illustration of this, whereby individuals experience subjectively real somatic symptoms despite the absence of any organic cause. The work in this thesis aimed to investigate how individuals experiencing somatic symptoms process multisensory information about the body and, more specifically, set out to test the hypothesis that symptom reporting is associated with a general tendency to over-weight top-down information during the process of body representation. The role of visual information in shaping bodily perception was explored by using visual manipulations that distorted the appearance of the body, introducing a discrepancy between sensory information and top-down knowledge about the body. The findings show that visual information can have a significant effect on the way in which the body is perceived, and also demonstrate that perception of the self arises from a dynamic interaction between top-down and bottom-up inputs (Chapters 2 and 3). Contrary to hypotheses, the results do not support suggestions that somatic symptom experience is characterised by disturbances in body representation; individuals who report a higher number of somatic symptoms were found to process multisensory information about the body in a comparable way to those who reported few symptoms, demonstrating that somatic symptom experience is not associated with abnormal processing of visual, spatial and temporal sensory information about the body (Chapters 4 and 5). Furthermore, there is no evidence to suggest that high symptom reporters rely more on top-down information during the process of body representation, even in the presence of strong contextual cues (Chapters 5 and 6). The final study also observed no relationship between somatic symptom reporting and interoceptive accuracy, indicating that high symptom reporters perceive and integrate both exteroceptive and interoceptive sensory information in a typical fashion (Chapter 6). Overall, this work uses experimental methods to explore a number of theoretical concepts proposed as relevant for unexplained symptoms, concluding that somatic symptom experience amongst the general population is not characterised by abnormal multisensory integration or disrupted body representation.